2010
DOI: 10.1111/j.1600-0560.2009.01402.x
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical chronic lymphocytic leukemia with atypical cutaneous presentation

Abstract: Chronic lymphocytic leukemia (CLL) involving skin is a rare but well-documented occurrence, mainly reported in advanced disease. In contrast, CLL presenting with skin lesions is exceedingly rare, only few reports existing to date. We report a 70-year-old man who presented with two non-pruritic, papular lesions on the lower abdomen and proximal thigh. Biopsies showed dense lymphohistiocytic infiltrates involving the reticular dermis and subcutis without epidermotropism consisting mostly of small, CD20 and PAX-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…In B‐CLL, cutaneous manifestations generally occur late in the course of disease and are variably seen (in 3‐45%) in patients ( ) . A specific cutaneous infiltrate of B‐CLL can appear as erythematous papules, plaques, nodules or large tumors.…”
Section: Differential Diagnosis Of Cauliflower Earsmentioning
confidence: 99%
“…In B‐CLL, cutaneous manifestations generally occur late in the course of disease and are variably seen (in 3‐45%) in patients ( ) . A specific cutaneous infiltrate of B‐CLL can appear as erythematous papules, plaques, nodules or large tumors.…”
Section: Differential Diagnosis Of Cauliflower Earsmentioning
confidence: 99%
“…Earlier work suggested that leukaemia cutis in patients with CLL conferred a poor prognosis, often followed by blast crisis and death . While this certainly is the case in Richter's syndrome (large cell transformation), it appears that patients with CLL infiltrates have a better prognosis than was originally thought . In the largest report of cutaneous infiltrates in CLL, the 5‐year survival in 42 patients was 66% .…”
mentioning
confidence: 91%
“…9 While this certainly is the case in Richter's syndrome (large cell transformation), it appears that patients with CLL infiltrates have a better prognosis than was originally thought. 7,10 In the largest report of cutaneous infiltrates in CLL, the 5-year survival in 42 patients was 66%. 7 The same study suggested that the mean duration of disease before skin manifestations was 39 months, and in seven patients, skin lesions were the first sign of disease.…”
mentioning
confidence: 99%
“…Although indolent, it is refractory to treatment with only allogeneic stem cell transplantation a curative option for selected patients. CLL involves the skin usually in its advanced stages [1]. We present an uncommon cutaneous presentation of CLL and review the literature on all similar cases.…”
mentioning
confidence: 95%